2013
DOI: 10.1021/jp4005746
|View full text |Cite
|
Sign up to set email alerts
|

Interference Energy in C–H and C–C Bonds of Saturated Hydrocarbons: Dependence on the Type of Chain and Relationship to Bond Dissociation Energy

Abstract: Interference energy for C-H and C-C bonds of a set of saturated hydrocarbons is calculated by the generalized product function energy partitioning (GPF-EP) method in order to investigate its sensitivity to the type of chain and also its contribution to the bond dissociation energy. All GPF groups corresponding to chemical bonds are calculated by use of GVB-PP wave functions to ensure the correct description of bond dissociation. The results show that the interference energies are practically the same for all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
3
16
0
2
Order By: Relevance
“…This is illustrated in Figures a‐b, for the LiH (μ= −5.882 D) and BH (μ=1.270 D) molecules. Moreover, this interference stabilization comes from the kinetic contribution, in agreement with previous studies . This is a strong evidence that, despite the difference of electronegativity between the atoms involved, all of the molecules described herein form typical covalent bonds.…”
Section: Two Electron Chemical Bondssupporting
confidence: 92%
See 2 more Smart Citations
“…This is illustrated in Figures a‐b, for the LiH (μ= −5.882 D) and BH (μ=1.270 D) molecules. Moreover, this interference stabilization comes from the kinetic contribution, in agreement with previous studies . This is a strong evidence that, despite the difference of electronegativity between the atoms involved, all of the molecules described herein form typical covalent bonds.…”
Section: Two Electron Chemical Bondssupporting
confidence: 92%
“… Energy profiles for dissociation of the C−H bond in methane and the C−C bond in ethane (Adapted from ref …”
Section: Two Electron Chemical Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify the generality of the IEA results, we examined different types of systems exhibiting distinct bonding patterns. Diatomic and polyatomic molecules, with single double and triple bonds, with different degrees of polarity, linear or branched, cyclic or not, conjugated and aromatics, as well as one‐electron bonds have been considered . In all cases, the conclusion was exactly the same: for each bond of a diatomic or polyatomic molecule, the results of the energy partitioning into interference and quasi‐classical contributions showed that the main contribution to the depth of the potential wells comes from the interference term and that its kinetic component is the responsible for the stability of the bond.…”
Section: Some Advantages Of Using Wave Functions That Account For Thementioning
confidence: 99%
“…Very recently, as mentioned earlier, Knizia et al have presented the intrinsic bond orbitals that can be associated with a non-empirical form of localized molecular orbitals to obtain the electron flow for reaction mechanisms. 75,[123][124][125] On the other hand, topological analysis is a useful tool to characterize intra-and intermolecular interactions, and different types of bonding analysis methods are based on the topology of scalar fields, 126 while different applications have already been published in the literature. The name 'quantum chemical topology' 136,137 has been introduced to embrace all topological investigations of three-dimensional scalar fields 46,[138][139][140][141][142][143][144] in order to rationalize the chemical bond and gain further understanding of the chemical reactivity.…”
Section: Quantum Chemical Topologymentioning
confidence: 99%